Analisis Yuridis Pembatalan Hak Untuk Melakukan Perkawinan Antara Sesama Pekerja Dalam Satu Perusahaan (Studi Putusan Mahkamah Konstitusi Nomor 13/PUU-XV/2017) - Olivia Sitanggang (Universitas Islam Sumatera Utara, 2020)
Currently, there are several companies that make regulations that require the workers to resign or even be willing to be laid off if they decide to marry another worker in the company. Some of the reasons are preventing personal conflict, subjectivity, corruption, collusion and nepotism. The formulation of the problem in this research is what is the background of the provisions regarding the prohibition of marriage between fellow workers in one company, how is the analysis of the judges legal considerations in the decision Number 13 / PUU-XV / 2017, what is the impact of the Constitutional Court decision on the inclusion of clauses prohibiting intermarriage between workers.The results showed that the background of the provisions concerning the prohibition of marriage between fellow workers in one company is to maintain a professional attitude of workers when carrying out their work in order to maintain the company's existence in the world of business competition. Another reason is that it refers to Article 153 paragraph (1) letter f of Law Number 13 of 2003 so that this provision is used as a reason for employers to prohibit marital ties for fellow workers in their company. The legal consideration of the judge in decision Number 13 / PUU-XV / 2017 is clear that Article 153 paragraph (1) letter f of the Labour Laws is no longer valid, because the phrase unless it has been regulated in a work agreement, company regulation, or collective working agreement is contrary to the Constitution 1945 and has no binding legal force. The impact of the Constitutional Court's decision on the inclusion of a clause on the prohibition of marriage is that employers cannot state the reasons for dismissal of workers who have marital ties to other workers in the same office in the employment agreements, company regulations or collective working agreements, so that if the entrepreneur includes it, it is considered to have violated the decision of the Constitutional Court. Keywords: Cancellation of the Rights, Marriage, Workers, One Company.